2020
DOI: 10.1016/j.ympev.2019.106637
|View full text |Cite
|
Sign up to set email alerts
|

Eocene–Oligocene cooling and the diversification of Hemidactylus geckos in Peninsular India

Abstract: The Eocene-Oligocene cooling marks a global shift towards a cooler and drier climate, concurrent with significant turnover in biota globally. In Peninsular India, palynological investigations suggest a shift from wet rainforest vegetation to dry and seasonal species during this period. However, the grassland and open habitats that dominate this region at present expanded relatively recently due to Late Miocene intensification of monsoon seasonality. We test the possible role of these climatic shifts in generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 94 publications
(114 reference statements)
0
21
0
Order By: Relevance
“…Each of the three dry zone clades overlaps in distribution with members of the Cyrtodactylus ( Geckoella ) collegalensis complex (Agarwal, 2016; Mirza, Pal, & Sanap, 2010), the south India clade of Hemiphyllodactylus (Agarwal, Khandekar, et al, 2019), and members of the Hemidactylus prashadi clade (Agarwal, Giri, et al, 2019). Cnemaspis is apparently absent from the northern Eastern Ghats, though the gekkonid genera Geckoella , Hemidactylus, and Hemiphyllodactylus, which are all younger entrants in peninsular India dating back to the Eocene–Oligocene, are distributed in the northern Eastern Ghats (Agarwal & Karanth, 2015; Agarwal, Khandekar, et al, 2019; Lajmi & Karanth, 2020). It remains unclear whether the absence of Cnemaspis in the northern Eastern Ghats is a sampling artifact or is linked to an inherent physiological, ecological, or other biogeographic constraint.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the three dry zone clades overlaps in distribution with members of the Cyrtodactylus ( Geckoella ) collegalensis complex (Agarwal, 2016; Mirza, Pal, & Sanap, 2010), the south India clade of Hemiphyllodactylus (Agarwal, Khandekar, et al, 2019), and members of the Hemidactylus prashadi clade (Agarwal, Giri, et al, 2019). Cnemaspis is apparently absent from the northern Eastern Ghats, though the gekkonid genera Geckoella , Hemidactylus, and Hemiphyllodactylus, which are all younger entrants in peninsular India dating back to the Eocene–Oligocene, are distributed in the northern Eastern Ghats (Agarwal & Karanth, 2015; Agarwal, Khandekar, et al, 2019; Lajmi & Karanth, 2020). It remains unclear whether the absence of Cnemaspis in the northern Eastern Ghats is a sampling artifact or is linked to an inherent physiological, ecological, or other biogeographic constraint.…”
Section: Discussionmentioning
confidence: 99%
“…The terrestrial ecomorphs have smaller body size and toepad size, as compared to the scansorial ecomorph. A study by Lajmi and Karanth (2019) found an early increase in lineage accumulation beginning ~36 Mya in this group. Furthermore, ancestral state reconstruction revealed that the ancestor of this radiation was a dry-biome lineage.…”
Section: Discussionmentioning
confidence: 54%
“…Currently, 39 species of Hemidactylus are described from the Indian radiation, of which 27 species have been included in this study. Additionally, five new putative species delimited as per Lajmi and Karanth (2019) have been added to the study. Details of the species and their habitat information are given in Table S2…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
See 2 more Smart Citations